Ten‐year long‐term results after non‐surgical management of hepatolithiasis, including cases with choledochoenterostomy. (29th July 2014) - Tsuyuguchi, Toshio; Miyakawa, Kaoru; Sugiyama, Harutoshi; Sakai, Yuji; Nishikawa, Takao; Sakamoto, Dai; Nakamura, Masato; Yasui, Shin; Mikata, Rintaro; Yokosuka, Osamu
Abstract Background Long‐term follow‐up of non‐surgical procedures for the management of hepatolithiasis has been reported, but risk factors for mortality have not been properly evaluated. Methods We conducted a retrospective study of the case records of 121 patients with hepatolithiasis who underwent endoscopic retrograde cholangiopancreatography (ERCP), peroral cholangioscopy (POCS), percutaneous transhepatic cholangioscopy (PTCS), or conservative treatment at the Department of Gastroenterology of Chiba University Hospital between January 1980 and July 2011. The primary outcome measure was mortality, defined as death due to hepatolithiasis (concomitant liver failure with cholangitis and cholangiocarcinoma). Results Complete clearance of intrahepatic stones was achieved in 22 (57.8%) of 38 patients by POCS, in 12 (66.7%) of 18 patients by ERCP, and in 10 (52.6%) of 18 patients by PTCS. The remaining 46 patients were treated conservatively. The mean follow‐up period was 11.4 ± 7.1 years (range, 0.6–32.8). There were 14 hepatolithiasis‐related deaths (11 with cholangiocarcinoma and three from liver failure with cholangitis) during the follow‐up periods. Multivariate Cox proportional hazards analysis revealed liver atrophy (P = 0.015; HR = 3.98; 95% CI, 1.30–12.20) and congenital biliary dilatation after biliary‐enteric anastomosis (P = 0.036; HR = 4.57; 95% CI, 1.11–18.87) as significant risk factors for mortality. Conclusions Analysis of the 10‐year long‐term results after non‐surgical management of hepatolithiasis identified liver atrophy and congenital biliary dilatation as risk factors for mortality. Patients with hepatic lobe atrophy should undergo a hepatectomy, if operable.